REMOVAL OF A FRACTURED POST AND RETREATMENT: CASE REPORT - Fahmi Mulya; Sri Kunarti (Journal of Syiah Kuala Dentistry Society, 2017)
A post that has fractured in a root canal can be a major problem in the endodontic retreatment. In such a situation the risk of root fracture or perforation during removal of the post remnant may be high. This case describe about solving the problem of fracture-post, removing the broken post in the canal, and retreatment of tooth. A 50 year old male patient came in to Department of Conservative Dentistry - Airlangga University with a chief complains fractured post-crown at maxillary central incisor. 2 years ago root canal treatment was performed. This post-crown fractured twice. These fractured posts can be loosened by using a ultrasonically with diamond-coated tip at the cement interface. The tip breaks up the luting cement with counter-clockwise motion and the irrigant washes it away, and this in turn helps removal with diamond-coated which is used to cut down along the cement. There are many factors that influence successful post removal such as operator judgment, training, experience, and utilizing the best technologies and techniques. Care must be taken to check the edges of the tip, sharpening them when necessary. Occasionally the edges can flare out, with resultant danger of excessive removal of dentin and increased risk of weakening the root or even perforation. Removal of the post leads to the risk of complications associated with the forming of ledges, perforations and fracture of the tooth root. For safe removal of the posts it is necessary to know and use appropriate armamentarium and suitable techniques.Keyword: removal of metal endodontic post, endodontic retreatment, ultrasonics